2014
DOI: 10.1126/science.1254445
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of muscular dystrophy in mice by CRISPR/Cas9–mediated editing of germline DNA

Abstract: Duchenne muscular dystrophy (DMD) is an inherited X-linked disease caused by mutations in the gene encoding dystrophin, a protein required for muscle fiber integrity. DMD is characterized by progressive muscle weakness and a shortened life span, and there is no effective treatment. We used clustered regularly interspaced short palindromic repeat/Cas9 (CRISPR/Cas9)–mediated genome editing to correct the dystrophin gene (Dmd) mutation in the germ line of mdx mice, a model for DMD, and then monitored muscle struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
466
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 619 publications
(493 citation statements)
references
References 37 publications
4
466
1
14
Order By: Relevance
“…Dominant disorders mostly result from heterozygous gain-of-function mutations; and the treatment requires removal or disruption of the mutant allele. The CRISPR/Cas9 gene-editing system has been successfully used to correct mutations in mouse zygotes [19,22] and to edit genes in the liver [20,21]. However, accurate repair of mutations has mostly been carried out in zygotes and embryos with a high efficiency of homologous recombination, which occurs infrequently in somatic tissues such as the cardiomyocytes; thus it has remained challenging to apply the CRISPR/Cas9 system to the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dominant disorders mostly result from heterozygous gain-of-function mutations; and the treatment requires removal or disruption of the mutant allele. The CRISPR/Cas9 gene-editing system has been successfully used to correct mutations in mouse zygotes [19,22] and to edit genes in the liver [20,21]. However, accurate repair of mutations has mostly been carried out in zygotes and embryos with a high efficiency of homologous recombination, which occurs infrequently in somatic tissues such as the cardiomyocytes; thus it has remained challenging to apply the CRISPR/Cas9 system to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The prokaryotic type II clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 genome-editing system, coupling the Cas9 nuclease with short guide RNAs (sgRNAs) [15][16][17][18], has been successfully applied to correct disease-causing mutations in the zygotes and livers [19][20][21][22]. In addition, adeno-associated virus (AAV)-based, CRISPR/Cas9-mediated excision of intervening DNA from the mutant dystrophin gene partially restored muscle structural and functional deficiencies in the mouse model of Duchenne muscular dystrophy (DMD) [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…3). In mice, CRISPR/Cas9 has been used to perform germline correction of multiple genetic diseases, including cataract and muscular dystrophy [21,22], and the technology was also used to make corrections in somatic cells. For example, in a mouse model of the human disease hereditary tyrosinemia, the CRISPR/Cas9 system was used to correct the underlying Fah mutation in hepatocytes.…”
Section: Application Of Crispr/cas9mentioning
confidence: 99%
“…Since its introduction into mammalian cells 2,3 and animals 4 about three years ago, CRISPR-Cas9 has been revolutionizing many fields of medical research and has been applied to the gene therapy explorations of many human diseases. [5][6][7][8][9] Recently, important progresses have been made in the gene therapy potentials of CRISPR-Cas9. Three studies [10][11][12] simultaneously published in Science reported the ability of CRISPR-Cas9 for in vivo gene therapy when delivered locally (intra-muscular) or systemically (intra-peritoneal or intravenous) into adult or neonatal mice with Duchenne muscular dystrophy (DMD), a disease model caused by a nonsense mutation in exon 23 of Dmd gene.…”
mentioning
confidence: 99%
“…By far, the most majority of therapeutic explorations using CRISPR-Cas9 are conducted in cells or animal germline to rectify, replace or delete the culprit genes. 5,6 However, the strategy of ex vivo gene correction followed by autotransplantation or allotransplantation is only applicable to a part of human diseases such as hematological malignancies and may require repeated episodes of treatment, and germline modification is currently unacceptable in humans. In 2014, Yin et al 8 reported in vivo gene correction in adult mice with hereditary tyrosinemia by hydrodynamic injection of therapeutic CRISPR-Cas9 components through tail-vein, but this approach remains inapplicable to humans due to its potential damages to liver and cardiovascular functions.…”
mentioning
confidence: 99%